Professionalism and personal integrity: a humble example in a humble fisherman - Maria Fransisca Andanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2021)
The paper addresses professionalism and personal integrity, what lies between them, how they connect each other, and what real example could be drawn into both issues. It discusses professionalism and personal integrity as proposed by Suseno (1991). It also highlights professionalism from Buddhist perspective. Finally, it analyzes professionalism and personal integrity in the character of Santiago, Hemingway’s The Old Man and the Sea (1952) as proposed by Khan (2014). The paper concludes that professionalism is not only about mastering certain skills and having certain knowledge, but it should be built based on personal integrity.